CapNet: A Real-Time Wireless Management Network for Data Center Power Capping - Saifullah, Abusayeed; Sankar, Sriram; Chandra, Ranveer; Priyantha, Bodhi; Lu, Chenyang; Liu, Jie (IEEE Real-Time Systems Symposium (RTSS), 2014)
Data center management (DCM) is increasingly becoming a significant challenge for enterprises hosting large scale online and cloud services. Machines need to be monitored, and the scale of operations mandates an automated management with high reliability and real-time performance. Existing wired networking solutions for DCM come with high cost. In this paper, we propose a wireless sensor network as a cost-effective networking solution for DCM while satisfying the reliability and latency performance requirements of DCM. We have developed Cap Net, a real-time wireless sensor network for power capping, a time-critical DCM function for power management in a cluster of servers. Cap Net employs an efficient event-driven protocol that triggers data collection only upon the detection of a potential power capping event. We deploy and evaluate Cap Net in a data center. Using server power traces, our experimental results on a cluster of 480 servers inside the data center show that Cap Net can meet the real-time requirements of power capping. Cap Net demonstrates the feasibility and efficacy of wireless sensor networks for time-critical DCM applications. See information about the event here.